The effects of different stretching and warm-up exercise protocols on 50-meter swimming performance in sub-elite women swimmers - Kafkas, A.; Eken, Ö.; Kurt, C.; Kafkas, M. E. (Isokinetics and Exercise Science, 2019)
BACKGROUND: Warm up exercises are common practice before training and competition in almost every sport. Although, swimming is a popular sport throughout the world, studies on the effects of warm-up are scarce. OBJECTIVE: The purpose of this study is to compare the effects of different stretching warm-up and exercise protocols on swim performance. METHODS: Fourteen sub-elite college women swimmers volunteered to participate in the study. The four stretching and warm-up protocols they followed were; (I) without stretching (WS); (II) static stretch (SS); (III) in-water (IW); and (IV) dry land (DL). RESULTS: There was a significant main effect for 50-meter front crawl (F = 70,453; p = 0.00) and breaststroke swimming performances (F = 145.504; p = 0.000). The best 50-meter front crawl and breaststroke performance detected immediately after IW was 28.1 and next, 39.9 seconds. Pairwise comparison indicated that the best 50-meter front crawl performance monitored after IW protocol was 28.0 ± 2.9 (p = 0.000) compared with that after WS - 29.8 ± 2.3 (p = 0.000) and after SS - 30.7 ± 2.2 (p = 0.000). CONCLUSIONS: Pre-event low-intensity IW warm-ups may be optimal for 50-meter front crawl and breaststroke swimming performance.